Equilibrium Unemployment in a General Equilibrium Model with Taxes. (September 2014) - Bhattarai, Keshab; Dixon, Huw
Abstract : With a dynamic computable general equilibrium model with Pissarides and Mortensen and Pissarides type equilibrium unemployment, impacts of tax‐transfer programmes are assessed for the UK. The model contains more desirable structure of households and production sectors and includes more type of shocks in preferences, technology, trade and policy instruments for stochastic analyses than is usual in dynamic stochastic general equilibrium (DSGE) models. It assesses growth and cycles as well as equity and efficiency effects of policies in the long run simultaneously. The labour–leisure and consumption–saving decisions impact more on growth and welfare of households with efficient matching making transitions to employment easier for job seekers.